A simple method for determining the thermal effusivity of defects. Issue 2 (5th June 2014) - Elhassnaoui, Ahmed; Saifi, Abderrahim; Elamiri, Asseya; Sahnoun, Smail
Abstract : In this article, a simple method was proposed for determining the thermal effusivity of defects using pulsed thermography. This method is complementary to other methods such as those that implement periodic thermal stresses for identification of the thermal properties of materials, or which use specific photothermal analysis or extended. Theoretically, this technique is based on solving the heat equation in the case of an isotropic solid heated by a delta Dirac pulse. The application conditions of this new technique have been studied by numerical simulations. A finite element modeling has been performed in the case of a steel sample which may contain geometry defects filled in by air, resin, oil, wax or water. The analysis of surface temperature distribution of the infected samples by the proposed method allowed to determine the thermal effusivity of defects. The experimental measurements have confirmed the importance and simplicity of this method in the characterization of defects using pulsed thermography. The results show the possibility of approaching, at an acceptable error, the defect thermal effusivity.